(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article analyzes the macroanatomy of retinal vessels in patients with early-stage type 2 diabetes mellitus using optical coherence tomography (OCT). The study involved 24 patients diagnosed with type 2 diabetes. The condition, thickness, perfusion level, and presence of microaneurysms in the retinal vessels were evaluated. The results obtained demonstrated the significance of OCT in early diagnosis and prevention of diabetic retinopathy.